Use of dental services in areas covered by the Family Health Strategy in Olinda, Brazil - Raquel Santos de Oliveira; Bruno Gama Magalhães; Paulo Sávio Angeiras de Góes; Renata de Andrade Cardoso Pinto Rocha; Gabriela da Silveira Gaspar (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2014)
OBJECTIVE:The aim of the present study was to analyze factors associated with the use of dental services in areas covered by the Family Health Strategy in the city of Olinda, northeastern Brazil.METHODS:A quantitative, analytical, cross-sectional study was conducted involving individuals over 18 years of age (n=492) registered at Family Health Units. Data analysis was performed with SPSS program (version 11.0) and involved 2 test and logistic regression analysis.RESULTS:The number of individuals who sought dentists at public services (58.6%) was greater than that who sought dentists in the private sector (37.4%). Among those who used public services in the previous 12 months, only 18.9% had access to a dentist from a Family Health Unit. Multiple logistic regression analysis showed that the use of services was associated with toothaches in the previous six months and living in a rented home (p<0.05).CONCLUSION:The results show that access to dental services was highly limited, even in areas covered by an Oral Health Team. Moreover, access was potentiated by indicators of oral health needs and socioeconomic status.